DEVELOPMENT OF A METHODOLOGY FOR ORGANIZING CLASSES OF GENERAL SECONDARY SCHOOLS BASED ON NEW TECHNOLOGIES - Yuldashev, Akmaljon (International Journal Multidisciplinary (IJMI), 2024)
In this article, the role of the music teacher in the development of music lessons in general secondary schools and the positive solution of the demands and obligations imposed on him are analyzed.